A Review of Research on Problematic Internet Use and Well-Being With Recommendations for the U.S. Air Force - Breslau, Joshua (RAND Corporation, 2015)
Problematic Internet Use (PIU) is a behavioral syndrome characterized by excessive and compulsive online activities, symptoms of tolerance and withdrawal, functional impairment and, often, other mental health problems. This report reviews the scientific literature on the epidemiology, prevention, and treatment of PIU with the goal of informing Air Force policies to curb PIU's negative impact on operations and the mental health of Airmen.